CRIMINAL LAW POLICY FOR FOREST PROTECTION IN INDONESIA (A STUDY ON FOREST DESTRUCTION CRIME IN MEDAN, NORTH SUMATERA) - Anita Zulfiani; Nabila Alinka Wibowo; Muna Ganesya Arya (GeoEco, 2026)
Indonesia's role is very important in preventing global temperature rise because Indonesia is considered the "lungs of the earth". Deforestation produces emissions that contribute to global warming. Most of the forest destruction in Indonesia is caused by illegal logging activities. Forests need to be protected. The purpose of writing this research is to analyze criminal law policies in protecting Indonesia's forests by conducting a study of criminal acts of forest destruction in Medan, North Sumatra. This research is normative or doctrinal legal research. This research concludes that the forest protection criminal law policy implemented by the Indonesian government involves the creation of legal and regulatory norms that regulate actions that constitute forestry crimes, accompanied by sanctions in the form of imprisonment and fines. These regulations are contained in the Forestry Law. In enforcing it, the Public Prosecutor also applies the Corruption Law to prosecute perpetrators of forestry crime. Protection of Indonesia's forests is not only carried out through the implementation of the Forestry Law but also through the implementation of the Corruption Law. By implementing the Corruption Law, perpetrators of forestry crimes are not only punished with imprisonment and fines. However, they are also required to pay compensation, which also takes into account the perpetrator's assets.